2012
DOI: 10.1002/lary.22411
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging surveillance following vestibular schwannoma resection

Abstract: Persistent nonspecific radiologic enhancement within the postoperative field is common, making the diagnosis of tumor recurrence challenging. Factors including completeness of resection and baseline postoperative MRI findings provide valuable information regarding risk for recurrence, which may assist the clinician in determining an appropriate postoperative MRI surveillance schedule. Future studies using standardized terminology and consistent study metrics are needed to further refine surveillance recommenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 30 publications
7
71
0
1
Order By: Relevance
“…Residual postoperative tumor thickness of 10.9 ± 4.1 mm versus 5.7 ± 3.0 mm has been shown to be a risk factor for regrowth (p < 0.001). 19 Carlson et al 6 reported that in 350 patients with VSs treated with microsurgical resection, patients receiving STR were more than 9 times more likely to experience recurrence compared with those undergoing NTR or GTR (p < 0.001). Whereas GTR is optimal to prevent tumor recurrence, NTR appears to provide similarly low recurrence rates, likely due to a lack of adequate blood supply or critical tumor mass following NTR to allow subsequent growth.…”
Section: Extent Of Resectionmentioning
confidence: 99%
“…Residual postoperative tumor thickness of 10.9 ± 4.1 mm versus 5.7 ± 3.0 mm has been shown to be a risk factor for regrowth (p < 0.001). 19 Carlson et al 6 reported that in 350 patients with VSs treated with microsurgical resection, patients receiving STR were more than 9 times more likely to experience recurrence compared with those undergoing NTR or GTR (p < 0.001). Whereas GTR is optimal to prevent tumor recurrence, NTR appears to provide similarly low recurrence rates, likely due to a lack of adequate blood supply or critical tumor mass following NTR to allow subsequent growth.…”
Section: Extent Of Resectionmentioning
confidence: 99%
“…15 Resection can be classified as gross total if there is no visible tumor remaining, near total if the remaining tumor dimensions are less than 5 × 5 × 2 mm, and subtotal if the remaining tumor is larger than that achieved after near-total resection. 4 Alternatively, neartotal resection can be designated as incomplete removal with less than 5% residual tumor volume and subtotal resection as greater than 5% of the original tumor volume. 7 Subtotal resection is associated with a 9 times greater likelihood of tumor recurrence compared with gross-total resection.…”
Section: Surgical Approachesmentioning
confidence: 99%
“…7 Subtotal resection is associated with a 9 times greater likelihood of tumor recurrence compared with gross-total resection. 4 Magnetic resonance imaging is routinely performed after resection, mainly to assess for residual or recurrent tumor, as well as suspected complications. A typical postoperative MRI examination consists of an internal auditory canal protocol that includes thin-section axial precontrast T1-weighted imaging, axial and coronal thinsection postcontrast fat-suppressed T1-weighted imaging, T2-weighted fast spin echo, T2-weighted FLAIR, diffusion-weighted imaging, and cisternography sequences, such as CISS (constructive interference in steady state) or FIESTA (fast imaging employing steady-state acquisition), at the level of the cerebellopontine angle.…”
Section: Surgical Approachesmentioning
confidence: 99%
See 2 more Smart Citations